"Moving from transactional government to enablement" in Indigenous service delivery: The era of New Public Management, service innovation and urban Aboriginal community development. Issue 3 (26th September 2018) - Howard‐Wagner, Deirdre
Abstract: Over the last 40 years, Aboriginal Community Based Organisations have played a distinctive role in society in relation to urban Aboriginal peoples and their rights to self‐determination and community development in the Australian city of Newcastle. They have proven essential to advocacy, the maintenance of community development, and the creation of new Aboriginal social infrastructure (community organisations, facilities, services, and supporting infrastructure). Autonomy has been empowering for local Aboriginal people. Major reforms to the delivery of government social services, particularly government enablement of a new social service market based on New Public Management principles, threaten this success. This interpretive, qualitative case study illustrates the effects of social service market enablement. It draws on a case study of the effects of social service market enablement on urban Aboriginal Community Based Organisations in Newcastle, showing the antagonistic relationship between social service market enablement and Aboriginal community enablement and development. It ends with a discussion of how Aboriginal community development in this city could be re‐enabled in light of the Prime Minister's arguments in his 2017 Annual Parliamentary Closing the Gap speech providing particular value in the context of policy discussions about moving from transactional government to enablement in Indigenous affairs.